Pull Factor and Push Factor Influences on the Volatility of Foreign Investment Flows in Indonesian Capital Market - Chakimatuzzahroh, Chakimatuzzahroh; Witiastuti, Rini Setyo (Management Analysis Journal, 2018)
The purpose of this study is to determine the factors that affect the flow of foreign investment into the Indonesian Stock Market that includes the factors of return, risk, and inflation derived from foreign markets/ global (push factor) and from the domestic market (pull factor). Testing is done by using analysis model Autoregressive Conditional Heteroscedasticity (ARCH) and Generalized Autoregressive Conditional Heteroscedasticity (GARCH). Testing is done with six estimation models among them ARCH, GARCH, ARCH-M (2,1), ARCH-M (2,2), Treshold Autoregressive Conditional Heteroscedasticity (TARCH), dan Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH). Using the significance of estimation parameters, goodness of fit model, Akaike’s Information Criterion test, Schwarz Information test, and ARCH effect test, found the best model is ARCH-M (2,1) estimation model. The results of testing with ARCH-M (2,1) model showed that the return and domestic risk (pull factor) significantly have a relation with the flow of foreign investment in Indonesia Stock Exchange, while return , risk, global inflation (push factor), and domestic inflation have no significant effect.